Negative correlation between TNF-α and triglyceride levels in patients with cerebral infarction (Annals of Medical Research, 2021)
Aim: To investigate the interactions between tumor necrosis factor-alpha (TNF-α) and blood lipid levels in patients with acutecerebral infarction.Materials and Methods: A total of 43 cerebral infarction patients who applied to the neurology and emergency department of our faculty were included in cross-sectional matched case-control study, and the results were compared with 41 controls who had similar age and comorbidities. In addition to fasting serum lipids, serum glucose, C-reactive protein and hemogram were analyzed as well. Classification of infarct was made. An enzyme-linked immunosorbent test was used to determine baseline plasma TNF-α levels at the time of first admission and potential correlations between the groups were analyzed.Results: Compared to the control group, the cerebral ischemia group had a higher median TNF-α level (23.53; range, 21.74-43.29 ng/L vs. 23.00; range, 20.62-37.34 ng/L); however, the difference was not significant (p > 0.05). Groups were similar regarding blood lipid values (p > 0.05). In the patient group, TNF-α level showed a negative correlation with triglyceride (TG) and TG / HDL cholesterol (HDL-C) (rho= -0.319 p= 0.037 and rho= -0.321 p= 0.036), whereas no significant correlation was determined in the control group (p > 0.05), on the other hand plasma level of TNF-α was positively correlated with the National Health Stroke Scale score (rho = 0.455 p = 0.002).Conclusions: Our cross-sectional study revealed an interaction between decreased TG and TG / HDL-C and a high concentration of TNF-α in cerebral infarction for the first time. The importance of our finding is that it provides useful preliminary information, which is necessary for further research in this field.